2007
DOI: 10.2337/db07-0812
|View full text |Cite
|
Sign up to set email alerts
|

Splanchnic Spillover of Extracellular Lipase–Generated Fatty Acids in Overweight and Obese Humans

Abstract: OBJECTIVE-Triglyceride-rich lipoproteins, primarily chylomicrons, can contribute to plasma free fatty acid (FFA) concentrations via spillover of fatty acids during intravascular hydrolysis into the venous effluent of some tissues. The present study was undertaken to determine whether spillover occurs in the splanchnic bed of humans.RESEARCH DESIGN AND METHODS-Arterial and hepatic venous blood was sampled in postabsorptive (n ϭ 6; study A) and postprandial (n ϭ 5; study B) obese humans during infusion of carbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
25
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 27 publications
5
25
1
Order By: Relevance
“…This finding is consistent with the known preferential liver uptake of intravenously administered fatty acid tracers in animals (10). It is also consistent with the higher NEFA spillover rate from circulating TG in the splanchnic vs. systemic circulation in humans (25) and with hepatic uptake of chylomicron remnants (13). The relatively high cardiac dietary fatty acid uptake that we observed is also consistent with significant myocardial uptake of circulating TG in humans (26).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This finding is consistent with the known preferential liver uptake of intravenously administered fatty acid tracers in animals (10). It is also consistent with the higher NEFA spillover rate from circulating TG in the splanchnic vs. systemic circulation in humans (25) and with hepatic uptake of chylomicron remnants (13). The relatively high cardiac dietary fatty acid uptake that we observed is also consistent with significant myocardial uptake of circulating TG in humans (26).…”
Section: Discussionsupporting
confidence: 79%
“…To our knowledge, this is the first study to report a method that can quantify dietary fatty acid absorption and assembly into chylomicron, their delivery into the thoracic duct, and their simultaneous distribution and uptake into all tissues and organs in humans. Although it has been possible in some instances to use an arteriovenous gradient even across the heart or liver circulation or visceral adipose tissue biopsies during abdominal surgery to determine circulating TG and/or NEFA metabolism in these internal organs in humans (16,21,25,26), these studies are very invasive and difficult to perform, making assessment of organ-specific metabolism of dietary fatty acids impossible in most situations. In addition, it has previously been impossible to simultaneously measure partition of dietary fatty acids in all internal organs in humans, a major advantage of the novel method described herein.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study in overweight and obese subjects, we found that more than half of systemic spillover occurs in the splanchnic bed (8); studies in dogs showed a strong relationship between fractional spillover and intracellular lipolysis in visceral fat (10). In the present study, insulin was infused during continuous meal absorption to induce suppression of adipose tissue lipolysis additional to that achieved by the meal.…”
Section: Discussionmentioning
confidence: 86%
“…Fractional spillover in various studies has been estimated to be about 30 -40% of LPLgenerated fatty acids (7)(8)(9) and, depending on dietary fat intake, could account for 25% or more of total FFA flux (7). We previously reported that the majority of spillover in overweight and obese humans occurs in the splanchnic bed, probably in visceral adipose tissue (8,10). Spillover correlates strongly with release of FFAs by intracellular lipases in visceral fat, suggesting that it is regulated by intracellular lipolysis (10).…”
mentioning
confidence: 94%
See 1 more Smart Citation